TINGKAT KEPUASAN KONSUMEN TERHADAP TANGGAPAN PERUSAHAAN PASCATINDAKAN KOMPLAIN MELALUI MEDIA CETAK - Yuliati, Lilik Noor; Anzola, Yuza (Jurnal Ilmu Keluarga dan Konsumen, 2009)
The aims of this research were to identify the consumer’s characteristics that do the complain act, to analyze the relation between consumer’s characteristics with the complaint action, to analyze the company’s conception with consumer’s satisfactory level, and to analyze factors influence consumer’s satisfaction level complaint after company’s response. The research was conducted from February to May 2008 in Jabodetabek, using descriptive design method. The data collected was primary and secondary data which analyzed descriptively and inferentially. Then, the data was processed by using Microsoft Excel and SPSS 13.0. The satisfaction level was obtained by measurement using scale interval. Statistical test used in this research were Spearman Correlation and Multiple Linear Regression. According to this research’s results showed that 18-40 year old male consumers with high education incline to do the complaint act. Products/services usually complained were those around services, quality, and transaction cases. Almost all consumers felt unsatisfied towards the company’s after complaint ‘conception. This unsatisfactory was caused by the company’s bad and ineffective conception. The company’s conception had a strong relationship with the satisfactory level. Factors influenced consumer’s satisfaction level after complaint were sex, education, and the company’s fast conception towards complaints.